Reproductive activity and morphometric assessment of three commercial species of sea cucumber (Echinodermata) from Karimunjawa National Park, Indonesia - Mustagfirin MUSTAGFIRIN; Diah Permata Wijayanti; Subagiyo SUBAGIYO (Society for Indonesian Biodiversity, 2021)
Abstract. Mustagfirin, Wijayanti DP, Subagiyo. 2021. Reproductive activity and morphometric assessment of three commercial species of sea cucumber (Echinodermata) from Karimunjawa National Park, Indonesia. Biodiversitas 22: 3333-3341. Sea cucumbers are benthic animals that have economic value and play an important role in the environment. Exploitation on large scale to fulfill high market demand, caused overexploitation. The number of sea cucumbers in Karimunjawa decreased as a result of limited management. There is no study conducted on the commercial sea cucumbers (Holothuria edulis, Pearsonothuria graeffei, and Bohadschia vitensis) in Nyamuk Island, Karimunjawa. The objectives of the research were to determine the morphometric assessment and the reproductive cycle of the three species. The morphometric assessment of weight showed that the weight of H. edulis ranges 247.3-2539g, P. graeffei 415.3-428.1g, and B. vitiensis 672.4-678.1g, respectively. The first maturity size of gutted body weight (GWB50) for H. edulis was 127.84g, P. graeffei 357.61g, and B. vitiensis 279.34g. The gonad somatic index (GSI) range 13.60-15.60% for H. edulis, 14.75-12.25% for P. graeffei and 10.83-14.57% for B. vitiensis. The result of gonad somatic index with a value above 10% means that it has entered the spawning phase. The above data indicated that the three commercial species spawned monthly, during new moon. It is likely that the spawning peak occurred when the temperature was increased. However, the pattern of reproductive activity in this study was limited at Nyamuk Island. Future studies are needed to observe whether there is a correlation between the increasing water temperature and the reproductive activity of the three sea cucumbers.